2014
DOI: 10.1016/j.neulet.2014.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Changes in FKBP5 expression and memory functions during cognitive–behavioral therapy in posttraumatic stress disorder: A preliminary study

Abstract: Posttraumatic stress disorder (PTSD) is characterized by hyperarousal, flashbacks, avoidance, and memory dysfunctions. Although psychotherapy improves the clinical symptoms, its effect on memory has not been explored. In addition, there is no information about gene expression changes related to hippocampal functions. We assessed PTSD patients (n=20) using the Wechsler Memory Scale-Revised (WAIS-R) and a paired associates learning (PAL) test, as well as changes in blood FK506 binding protein (FKBP5) mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…This is consistent with our previous reports that low CB2R function induces depression-like symptoms in the mouse model and alcohol addiction in human population [ 3 ]. FKBP5/Fkbp5 is one of the biomarkers for posttraumatic stress disorder (PTSD): The FKBP5 gene expression was reported to be low but elevated during cognitive behavioral therapy (CBT) in PTSD patients [ 37 , 38 ]. Consistent with the PTSD study, the results from our experiments using a mouse model demonstrated a reduction of the Fkbp5 gene expression after CMS.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous reports that low CB2R function induces depression-like symptoms in the mouse model and alcohol addiction in human population [ 3 ]. FKBP5/Fkbp5 is one of the biomarkers for posttraumatic stress disorder (PTSD): The FKBP5 gene expression was reported to be low but elevated during cognitive behavioral therapy (CBT) in PTSD patients [ 37 , 38 ]. Consistent with the PTSD study, the results from our experiments using a mouse model demonstrated a reduction of the Fkbp5 gene expression after CMS.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous small studies have applied a similar approach to identify epigenetic changes associated with cognitive behavioral therapy and found increases in blood FKBP5 mRNA expression following therapy. 62,63 FK506-binding protein was included in the set of target genes for our study, but no significant change in expression level was detected. Future studies might examine whether there are distinct epigenetic pathways shared by both EFT and cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a genetic variant in the PAC1 receptor (ADCYAP1R1; rs2267735) was found to be associated with PTSD [54,55]. Of particular interest were the findings that a genetic variation of the glucocorticoid receptor cochaperone protein, FKBP5, moderates risk of developing PTSD in childhood abuse cases [56][57][58][59][60][61]. Binder and colleagues found that 4 SNPs in FKBP5 (rs9296158, rs3800373, 1360780, rs9470080) interacted with child abuse severity to predict adult PTSD symptoms [62].…”
Section: Hpa Axis Candidate Genesmentioning
confidence: 99%